SEMIOTIC ANALYSIS OF BLACK PEOPLE’S DISCRIMINATION IN REBECCA HALL MOVIE “PASSING” - Khatimah, Khusnul (Journal of English Literature and Linguistic Studies, 2025)
This study aims to investigate what types of discrimination are experienced by black people depicted in the "Passing" movie and the researcher also explores and examines the symbols and signs of discrimination against black people in the “Passing” movie. The qualitative descriptive method is the method that researchers use in this study. This research produced several findings. There are 2 types of discrimination depicted in the "Passing" movie, namely direct discrimination and indirect discrimination. Including racial, gender, social, economic, cultural and other discrimination. From this type of discrimination, the researcher found the denotative meaning depicted in the "Passing" movie namely limited public facilities for black people, education that was mapped out specifically for white people, ridiculed as dirty or Negro. The connotative meaning contained in the movie “Passing” is that white people still look down on black people. Considers all black people the same so that there is no need to name them, only need to mention one word that is Negro, and still think black people are dirty just because of their dark skin. The myth contained in the "Passing" movie is in the mention of the word Negro for black people that has existed for 200 years, and is still used today. hating and not wanting to be close to black people just because they think black is dirty, the stereotype of black being dirty itself has existed since the late 18th century through advertisements for Pears soap and until now there are still people who think black people are dirty.